IMPROVEMENT AND RESULT TRACKING OF THE SPECIAL RESISTENCE OF THE WRESTLERS AS AN ALTITUDE RESPONSE - Mališa Radović; Goran Kasum (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2008)
In the system of preparations for top-level sportsmen for grand competitions, impor tant place has training in the conditions of middle altitude mountains. In that condi tions it develops complex of adaptation reactions /fi rst of all the lack of oxygen/,that brings to improvement of functional possibilities of organism for competitions in lowland con ditions. In order to achieve high results, during the training in the mountains, it is important to fi nd the most effi cient way for use of environment conditions. It was deducted that adapta tion to the mountains conditions and development of the effi ciency of high quality wrest ling sportsmen it defers from less successful wrestlers. Repetition of staying in moun ted areas enables faster adaptation and offers possibility for use of high physical uti li zation.